Youth Unemployment Problem In India: An analysis of youth unemployment and underemployment in India (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Increase in the shareof youth population due to demographic ‘dividend’ or the ‘youth bulge’ seems tobe one of the sources of future economic growth in India. Although withincrease in school and college enrolment rates, the proportion of youth in thelabour force has been declining, their high proportions in the labour forceindicate that the problem of youth unemployment and underemployment wouldremain a serious policy issue for many more years to come in India. In thiscontext, this paper examines the employment and unemployment situation of theyouth in India. It analyses the trends in labour force and workforce participationrates, unemployment, joblessness, working poor, growth and employmentelasticities etc. The paper also offers policy recommendations for increasingproductive employment and reduction in unemployment for the youth. The pooremployability of the workforce would hamper the advantages due to demographicdividend if measures are not taken to improve the educational attainment andskill development of the youth.